Assessment of microcirculation variables and endothelial glycocalyx using sidestream dark field videomicroscopy in anesthetized dogs undergoing cardiopulmonary bypass - Diaz, Devon M.; Orton, E. Christopher; de Rezende, Marlis L.; Zersen, Kristin; Guillaumin, Julien (Frontiers in Veterinary Science, 2023)
To evaluate microcirculation and endothelial glycocalyx (eGC) variables using sidestream darkfield (SDF) videomicroscopy in canine cardiopulmonary bypass (CPB).Methods: Dogs undergoing CPB for surgical correction of naturally-occurring cardiac disease were prospectively included. Variables collected included patient demographics, underlying cardiac disease, red blood cell flow (Flow), 4-25µm vessel density (Density), absolute capillary blood volume (CBVabs), relative capillary blood volume (CBVrel) and eGC width assessed by perfused boundary region (PBR). Anesthetized healthy dogs were used as control.Microcirculation and eGC variables were compared at baseline under anesthesia (T0), on CPB prior to cross clamping (T1), after cross clamp removal following surgical correction (T2) and at surgical closure (T3).Results: Twelve dogs were enrolled, including 10 with a complete dataset. Median Flow was 233.9, 79.9, 164.3, and 136.1 µm/s at T0, T1, T2, and T3 respectively (p=1.00). Median Density was 173.3, 118.4, 121.0 and 155.4 mm/mm 2 at T0, T1, T2, and T3 respectively (p=1.00). Median CBVabs decreased over time: 7.4, 6.6, 4.8 and 4.7 10 3 µm 3 at T0, T1, T2, and T3 respectively (p<0.01). Median CBVrel increased over time: 1.1, 1.5 ,1.1, and 1.3 10 3 µm 3 at T0, T1, T2, and T3 respectively (p<0.001). Median PBR increased over time: 1.8, 2.1, 2.4, 2.1 µm at T0, T1, T2, and T3 respectively (p<0.001). Compared to control dogs (n=8), CPB dogs had lower CBVabs at T0.Alterations in eGC thickness and microvascular occur in dogs undergoing CPB for naturally-occurring cardiac disease.eGC -Endothelial glycocalyx CPB -Cardiopulmonary bypass SDF -Sidestream dark field Density -total 4-25µm vessel density Flow -red blood cell flow CBVabs -absolute capillary blood volume CBVrel -relative capillary blood volume PBR -Perfused Boundary Region IV -Intravenous CRI -Constant Rate Infusion